2022
DOI: 10.1093/ofid/ofac511
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Metagenomic Next-Generation Sequencing in Leishmaniasis Diagnosis: A Case Series and Literature Review

Abstract: Background Leishmaniasis is a zoonotic disease caused by Leishmania spp. and spreads through sandfly bites. Owing to the wide range of nonspecific clinical symptoms, patients with leishmaniasis are frequently misdiagnosed or underdiagnosed. Methods The study participants were seven metagenomic next-generation sequencing (mNGS)-diagnosed patients with leishmaniasis who could not be diagnosed using conventional methods. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The rapid turnaround time of 2-3 days for obtaining pathogenic evidence with mNGS is particularly advantageous compared to the average feedback time of 7-14 days for culture-based methods. This expedited diagnosis supports the recognition of mNGS as a valuable tool for early and rapid disease diagnosis in clinical practice (Aoki and Kushimoto, 1987;Swenson et al, 2018;Han, 2022). Additionally, our study highlights another advantage of mNGS, which is its ability to directly target specific NTM strains without the need for further strain typing.…”
Section: Pcr Testing Resultssupporting
confidence: 76%
“…The rapid turnaround time of 2-3 days for obtaining pathogenic evidence with mNGS is particularly advantageous compared to the average feedback time of 7-14 days for culture-based methods. This expedited diagnosis supports the recognition of mNGS as a valuable tool for early and rapid disease diagnosis in clinical practice (Aoki and Kushimoto, 1987;Swenson et al, 2018;Han, 2022). Additionally, our study highlights another advantage of mNGS, which is its ability to directly target specific NTM strains without the need for further strain typing.…”
Section: Pcr Testing Resultssupporting
confidence: 76%
“…Owing to the wide range of non-specific clinical symptoms, patients with leishmaniasis frequently could not be diagnosed using conventional methods. For example, in seven patients whose blood mNGS findings pointed to Leishmania infection and were finally diagnosed with leishmaniasis, only three individuals tested positive for rK39, and two had Leishmania amastigotes identified in their bone marrow (12). In the two cases of this study, bone marrow aspirate smears failed to find Leishmania before mNGS detection, because of short…”
Section: Figurementioning
confidence: 66%
“…Conventional detection methods typically take several years to complete human genome sequencing, whereas mNGS can be completed in about a week. This not only dramatically improves the speed and accuracy of sequencing but also provides necessary technical support for identifying difficult, emerging, or newly discovered pathogens (10,11). In this study, it was suggested that out of 56 patients, 42 pathogens were identified.…”
Section: Discussionmentioning
confidence: 93%